Energy transfer from phycobilisomes to photosystem I at 77 K - van Stokkum, Ivo H. M.; Akhtar, Parveen; Biswas, Avratanu; Lambrev, Petar H. (Frontiers in Plant Science, 2023)
Picosecond time-resolved fluorescence was recorded at wavelengths of 605-760 nm in isolated photosystem I (PSI), phycobilisomes and intact cells of a PSII-deficient mutant of Synechocystis sp.PCC 6803 at 77 K to study excitation energy transfer and trapping. By means of a simultaneous target analysis of the kinetics of isolated complexes and whole cells, the pathways and dynamics of energy transfer in vitro and in vivo were established. We establish that the timescale of the slowest equilibration between different terminal emitters in the phycobilisome is ≈800 ps. It was estimated that the terminal emitter in about 40% of the phycobilisomes transfers its energy with a rate constant of 42 ns −1 to PSI. This energy transfer rate is higher than the rates of equilibration within the phycobilisome -between the rods and the core or between the core cylinders -and is evidence for the existence of specific phycobilisome-PSI interactions. The rest of the phycobilisomes remain unconnected or slowly transferring energy to PSI.